2020
DOI: 10.5194/acp-2020-141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Size-resolved exposure risk of persistent free radicals (PFRs) in atmospheric aerosols and their potential sources

Abstract: <p><strong>Abstract.</strong> Environmentally persistent free radicals (EPFRs) are a new type of substance with potential health risks. EPFRs are widely present in atmospheric particulates, but there is a limited understanding of the size-resolved health risks of these radicals. This study first reported the exposure risks and source of EPFRs in atmospheric particulate matter (PM) of different particle sizes (< 10 μm) in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For example, Yang et al (2017b) detected the EPFRs in different size of ne particulate matter during haze days in winter in Beijing with concentration ranging from 1.49 to 1.95×10 20 spins/g, and found the particulate matter with aerodynamic diameters < 1 µm had a highest EPFRs level. Chen et al (2020) also found the level and type of EPFRs in ne particulate matter (< 2.1 µm) are different with those in coarse particles (2.1-10 µm). Other studies also found the EPFR levels in airborne particulate matter in different cities, such as Taif, Saudi Arabia, Denver, United States and Xuanwei, China (Runberg et al, 2020;Shaltout et al, 2015;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…For example, Yang et al (2017b) detected the EPFRs in different size of ne particulate matter during haze days in winter in Beijing with concentration ranging from 1.49 to 1.95×10 20 spins/g, and found the particulate matter with aerodynamic diameters < 1 µm had a highest EPFRs level. Chen et al (2020) also found the level and type of EPFRs in ne particulate matter (< 2.1 µm) are different with those in coarse particles (2.1-10 µm). Other studies also found the EPFR levels in airborne particulate matter in different cities, such as Taif, Saudi Arabia, Denver, United States and Xuanwei, China (Runberg et al, 2020;Shaltout et al, 2015;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 82%
“…Missing values and uncertainty were input by the median concentration of the component and four times the median values to decrease their in uence on the results (Chen et al, 2020;Qian et al, 2020;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81−85 Therefore, herein, we also estimated the exposure risk by inhaling the equivalent number of cigarette tar EPFRs per day and night to assess the potential human risk (Figure 5g). 83,85,86 The results showed the seasonal average of EPFRs day/night in PM 10 and PM 2.5 exposure as winter: 1.66 ± 1.68; 1.33 ± 1.39; spring: 0.99 ± 1.06; 0.91 ± 1.42, whereas the average exposure amount of EPFRs per day and night in Xi'an were 1.24 and 1.37 cigarettes, which in total was equal to 452.6 and 500.05 cigarettes per year/ person. Compared to the study reported by Gehling and Dellinger, 2013a, 83 our results were five times higher.…”
Section: Day and Nighttime Variation Of Oxidative Potential (Op)mentioning
confidence: 99%